2004
DOI: 10.1111/j.1444-0903.2004.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

High rate of complications associated with peripherally inserted central venous catheters in patients with solid tumours

Abstract: The present study demonstrates a high rate of complications, which is higher than the complication rates reported in studies of non-oncology patients. PICC lines should be used with caution in patients with solid tumours. Prospective studies of the factors influencing the incidence of complications might be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
8
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 11 publications
4
67
8
2
Order By: Relevance
“…Premature PICC removal rate in our study, representing a definitional complication related end point particularly in the retrospective setting, was also similar to that in other settings (5,(16)(17)(18). However, most of the premature PICC removals in the present study were self-removals.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Premature PICC removal rate in our study, representing a definitional complication related end point particularly in the retrospective setting, was also similar to that in other settings (5,(16)(17)(18). However, most of the premature PICC removals in the present study were self-removals.…”
Section: Discussionsupporting
confidence: 86%
“…The total complication rate in our study was less than that of general cancer patients (16)(17)(18), and similar to that of non-cancer patients (5,8). Premature PICC removal rate in our study, representing a definitional complication related end point particularly in the retrospective setting, was also similar to that in other settings (5,(16)(17)(18).…”
Section: Discussionsupporting
confidence: 82%
“…Thrombotic complication in the present study was less as compared to Walshe L.J. et al [3], Cheong et al [4] and Chu et al [6]. This discrepancy in the result could be because in the present study before every catheter insertion, bleeding and coagulation profile was routinely checked and only those with normal study were offered insertion.…”
Section: Discussioncontrasting
confidence: 64%
“…In the present study the complication rate was seen more in haematological group while a retrospective study conducted by K. Cheong et al [4] showed more complications in solid tumour group, this discrepancy could be because of prolong hospitalisation, long duration of chemotherapy and use of steroid in haematological malignancies than solid tumour.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation